Faktor pendorong purchase intention produk sustainable fashion pada UMKM - Rike Penta Sitio; Rosita Fitriyani; Anggun Pesona Intan (Jurnal Manajemen Maranatha, 2021)
The creative fashion industry is one of the sources of economic strength in great demand by businessman and consumers, such as MSMEs. The purpose of this study was to examine the effect of consumer knowledge on purchase intention in MSMEs sustainable fashion products with trust as a mediator variable. The research method will use quantitative research. The samples obtained were 257 consumers of Indonesian MSMEs fast fashion products and used the Qualtrics electronic questionnaire. This research data is from perception data for sustainable fashion knowledge variables, trust, and purchase intention in MSMEs sustainable fashion products. The data were processed using SPSS to test the validity, reliability, regression analysis and mediation test using JASP. The results obtained are that consumers who know sustainable fashion will make these consumers more confident in sustainable fashion MSMEs products and ultimately increase consumer purchase intention in MSMEs sustainable fashion products. So it is very important for MSMEs engaged in the sustainable fashion business to educate consumers about the meaning of sustainable fashion and the practice of MSMEs in a sustainable fashion.